2017
DOI: 10.1177/0020764017735347
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness stigma among medical students and teachers

Abstract: Educators should pay closer attention to the role of medical psychology and communication training implementation, which may be beneficial to improving skills and increasing medical students' self-esteem and feeling of competence throughout their psychiatry rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 32 publications
3
32
0
4
Order By: Relevance
“…Our results suggest that psychiatry classes and specialized training could su ciently improve medical students' attitudes su ciently. Our nding that female medical students had less negative attitudes toward schizophrenia patients than their male counterparts supports the previous studies that found that women displayed less stigmatization of mental diseases than men [15,26]. Contrary to some previous studied [13,15], in our study neither personal experience with mental illness nor having a friend or family member with mental illness in uenced medical students' attitudes toward schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
“…Our results suggest that psychiatry classes and specialized training could su ciently improve medical students' attitudes su ciently. Our nding that female medical students had less negative attitudes toward schizophrenia patients than their male counterparts supports the previous studies that found that women displayed less stigmatization of mental diseases than men [15,26]. Contrary to some previous studied [13,15], in our study neither personal experience with mental illness nor having a friend or family member with mental illness in uenced medical students' attitudes toward schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are in accordance with the literature, which established that both theoretical education and contact with people suffering from mental diseases are effective factors in changing attitudes and stigma during psychiatrics internships. 4 10 11 12 14 15 17 18 19 Results reinforce the importance of a prolonged contact, in more than 1 moment, integrating the subjects in different years and multiple classes in each year. 36 37…”
Section: Discussionsupporting
confidence: 58%
“…Several recent studies suggest that psychiatry clerkship training has a positive effect in reducing stigma toward mental illnesses. 14 15 16 17 18 19 20 The impact of different populations and student-based interventions was also accessed, showing improvements in the attitudes in a short-term evaluation. In a long-term follow-up, results are, however, inconsistent, showing a decrease in the initial benefits of the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, this group was considered to be immune to these cognitive, emotional, and behavioral modalities toward people with psychiatric disorders (Lauber et al, 2004). However, recent studies have shown that there is little, if any, distinction between public and professional beliefs regarding mental illness (Bannatyne & Stapleton, 2017;Bannatyne & Stapleton, 2015;Jorm, 2000): stigmatization of people with mental illness is as much present in health care professionals as in the general population (Janouskova et al, 2017;Mittal et al, 2014;Saridi et al, 2017;Winkler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%